Nationalization and Foreign Direct Investment in Venezuela in the Era of President Nicolas Maduro Ramos - Miavania, S.; Arie, Kusuma Paksi (Technium Social Sciences Journal, 2022)
Venezuela has been famous of its petroleum source, and is right to be claimed for 90% of the country’s economy income since decades. Thus, Venezuela under President Chavez lead its economy through Petroleum and is seen to nationalize the economy policy. After switching from Chavez to Maduro, Venezuela is experiencing a multidimensional crisis rooted in political instability which then threatens every point of the country’s sovereignty. The fact that Nicolas Maduro is following in the footsteps of Chavez, who is anti-imperialist, has made Venezuela the target of sharp criticism from the world, especially the United States and its allies. Venezuela in fact, with its oil resources, ultimately does not want to be driven by the US or western imperialism. This paper focuses on explaining how the nationalization policy in the Nicolas Maduro era affected the country’s FDI. This case is written by using qualitative method that collect data from article, journal, dissertation, website and any other library resources. This paper is analyzed using the concept of nationalization to build a perspective. The results of this study indicate that political tensions have caused divisions and multidimensional crises in Venezuela. During the government of Nicolas Maduro, along with the policy of nationalization of foreign companies being continuously implemented, FDI inflows were also almost non-existent. Maduro refuses any foreign aid from the West. FDI is only received from socialist countries, in this case, China.